2000
DOI: 10.1046/j.1365-3040.2000.00589.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological factors limit fruit set of tomato (Lycopersicon esculentum Mill.) under chronic, mild heat stress

Abstract: The effects of chronic, mild heat stress on fruit set, fruit production, release of pollen grains, photosynthesis, night respiration and anther dehiscence were examined in tomatoes (Lycopersicon esculentum Mill.) differing in high-temperature sensitivity. Plants were grown under three temperature regimes: (1) 28/22 or 26/22 °C (optimal temperature); (2) 32/26 °C (high temperature); and (3) 32/26 °C day/night temperatures relieved at 28/22 °C for 10 d before anthesis, then returned to 32/26 °C (relieving treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
217
1
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(253 citation statements)
references
References 31 publications
18
217
1
9
Order By: Relevance
“…Given the previously reported correlation between PV and fruit set under LTMH (e.g. Dane et al 1991;Sato et al 2000;Xu et al 2017b), we conclude that wild germplasm might indeed be a valuable resource to enrich domesticated germplasm for reproductive thermotolerance.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Given the previously reported correlation between PV and fruit set under LTMH (e.g. Dane et al 1991;Sato et al 2000;Xu et al 2017b), we conclude that wild germplasm might indeed be a valuable resource to enrich domesticated germplasm for reproductive thermotolerance.…”
Section: Discussionsupporting
confidence: 68%
“…The reduction in tomato yield under long-term mild heat (LTMH) may be attributed to the plant's vulnerability during reproductive development, resulting in a lower number of pollen per flower (PN) and pollen viability (PV) (Dane et al 1991;Firon et al 2006;Kinet and Peet 1997;Levy et al 1978;Peet et al 1998;Pressman 2002;Pressman et al 2006;Sato et al 2000Sato et al , 2006Xu et al 2017b). In this study, we analysed the natural variation of reproductive thermotolerance in wild tomato species, which may serve as gene sources for cultivated tomato.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anther dehiscence that leads to pollen release is a complex process requiring successive cell differentiation and degeneration of specific tissues (Sato et al, 2000). The cell wall was the highest represented functional category among the 76 HsfA2-regulated genes, including genes encoding for enzymes related to cell wall remodeling, such as pectin methylesterases, pectin acetylesterases, and pectate lyases (Supplemental Table S6).…”
Section: The Contribution Of Hsfa2 In Pollen Thermotolerancementioning
confidence: 99%
“…In a different series of experiments carried out in common bean (Phaseolus vulgaris L.) (Prasad et al, 2002) and groundnut (Arachis hypogaea L.) (Prasad et al, 2003), and characterizing the Page 7 of 24 A c c e p t e d M a n u s c r i p t 7 combined effect of high temperatures and CO2, the beneficial effect of CO2 increase on vegetative growth and photosynthesis was not sufficient to offset the negative effects of high temperature on reproductive processes and yield. In tomato, although moderately elevated temperature stress (METS; 32/26ºC) did not cause significant changes in biomass, photosynthesis, and night respiration, fruit set was significantly reduced (Sato et al, 2000). In some studies of floral abortion under temperature stress, the observed reduction in carbohydrate supply to the reproductive tissues was attributed rather to reduction in sink demand (e.g.…”
Section: Flowering Stage Sensitivity To Temperature Fluctuationsmentioning
confidence: 99%